Assessing the effectiveness of management measures in the Ria Formosa coastal lagoon, Portugal - Newton, Alice; Cañedo-Argüelles, Miguel; March, David; Goela, Priscila; Cristina, Sónia; Zacarias, Marta; Icely, John (Frontiers in Ecology and Evolution, 2022)
The Ria Formosa is an important transitional and coastal lagoon on the south coast of Portugal that provides valuable ecosystem services. The lagoon is a protected area under national and international conventions. There is a great potential for Blue Growth sectors, such as aquaculture and coastal tourism, but these rely on good water quality. European environmental legislation, such as the Water Framework Directive, requires member states, such as Portugal to implement management measures if a surface water body is not of good ecological status. This work addresses the effectiveness of management measures, such as wastewater treatment plant implementation and dredging, on the water quality of the Ria Formosa coastal lagoon system. This is an important social-ecological issue, since management measures can be very expensive. The ecological status of Ria Formosa was evaluated, according to the physico-chemical and biological quality elements of the Water Framework Directive. The main indicators were the physico-chemical quality elements of nutrient and oxygen condition, and the biological quality element chlorophyll a, as a proxy for phytoplankton biomass, under the Water Framework Directive. The data for these quality elements from the Ria Formosa were analyzed for consistency with the classification for the Water Framework Directive water bodies. The data after the implementation of management measures was compared with historical data to evaluate if these measures had been effective. The relation between nutrient pressures, meteorological and hydrological conditions was addressed, especially rainfall and runoff. Results showed a decrease in nutrient concentration after the management interventions, despite the increase of population and intensifying agriculture in the catchment. The Ecological Status is spatially variable with an overall moderate status, indicating the need for further management measures. There is a significant reduction in nutrient pressure on the lagoon during drought years. This indicates that climate change may alter the structure and function of the lagoon in the future.